Penerapan TaRL dan Pembelajaran Berdiferensiasi dalam Meningkatkan Hasil Belajar Siswa SMP Qur’an Cahaya - Maharani, Ika Dewi Fitria; Setyaningrum, Wahyu (Mandalika Mathematics and Educations Journal, 2025)
This study explores the implementation of the Teaching at the Right Level (TaRL) approach combined with differentiated instruction to teach integers to seventh-grade students at SMP Qur’an Cahaya, Bangka Selatan, in July of the 2025/2026 academic year. A total of 17 students with varying levels of mathematical understanding participated in the study. The intervention began with a diagnostic assessment to identify students’ initial comprehension levels. Based on the results, students were grouped into three levels: basic, intermediate, and advanced. The basic group used a cardboard number line and toy sharpeners to compare and order integers. The intermediate group practiced adding and subtracting integers using integer cards, while the advanced group solved contextual word problems involving integers. The learning model used was Numbered Heads Together (NHT), where students were assigned numbers at the beginning of the lesson and randomly selected to present their group’s discussion outcomes. Following the learning activities, students completed a post-test and reflection session. The results indicated a significant improvement in student performance and a positive response toward learning in groups tailored to their ability levels. The integration of TaRL and differentiated instruction proved effective in fostering an inclusive, engaging, and student-centered learning environment that accommodated individual learning needs.